Continuous crossover(s) events of HIV-1CRF01AE and B subtype strains in Malaysia: evidence of rapid and extensive HIV-1 evolution in the region - Lau, K.A.; Wang, B.; Kamarulzaman, A.; Ng, K.P.; Saksena, N.K. (2008)
The Asian HIV epidemic appears to be complex, characterized by the prevalence of multiple subtypes and circulating recombinant forms with gradual replacement of pure HIV-1 subtypes in several geographical regions. The main objectives of the present study are to identify and analyse the full-length viral genomes of three unique recombinant forms (URFs); the HIV-1 isolates 07MYKLD47, 07MYKLD48 and 07MYKLD49 from Malaysia. Long-range polymerase chain reaction (PCR) amplification of seven overlapping reading frames was used to derive near full-length HIV-1 genomes. Detailed phylogenetic and bootscanning analyses were performed to determine phylogenetic associations and subtypic assignments. We further confirmed the mosaic composition of these CRF01AE/B inter-subtype recombinant forms, which are composed of B-subtype fragment(s) in the backbone of CRF01AE. Both 07MYKLD47 and 07MYKLD48 have an insertion of B subtype (880 bp and 532 bp) in the gag-pol and gp41-env gene regions, respectively. Whereas the isolate 07MYKLD49 has three B-subtype fragments inserted in different gene region along the genome; one each in the gag-pol (1862 bp) and pol-vif (1935 bp) regions, and a short B-subtype insertion (541 bp) in the 5' LTR-gag region. This highlights the public health relevance of newly emerging second generation HIV-1 recombinant forms and their dispersal, along with their rapid and continuous evolution in the region.